BAKTERI AEROB DAN BAKTERI PENYEBAB PENYAKIT DI neonATAL InTenSIve CARe unIT - Suriyanti Suriyanti; Irda Handayani; Benny Rusli (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2014)
Infectious diseases are still the main problem due to the potency of life threatening for neonates. Patients in the Neonatal Intensive Care Unit (NICU) are at risk for nosocomial infections resulting from the exposure to invasive procedures and medical equipments such as ventilator, catheter, Continuous Positive Airway Pressure (CPAP), incubator and antibiotics treatment. This study was aimed to know the related condition in NICU Dr. Wahidin Sudirohusodo Hospital Makassar by identification and determining the pathogenic bacteria colony counts of incubator and CPAP. The study design was a cross sectional method, by using incubator and CPAP as sample instruments, both equipments were sterilized at the NICU. The samples were collected and evaluated in July 2011. Samples were collected by usinga swab which was wiped to the instrument and put into Buffer Phosphate Saline (BPS); then diluted and put into Plate Count Agar (PCA) media for culture. The result of this study showed that there were no bacteria colony in the incubator, while in CPAP Acinetobacter calcoaceticus with bacteria colony count approximately 3.4×102 CFU/m3 were found. The researchers concluded that the incubator was sterile to bacteria, however in the CPAP bacteria from the strain of Acinetobacter calcoaceticus were found